A systematic review and meta-analysis of Lactobacillus acidophilus and Lactobacillus bulgaricus for the treatment of diarrhea - Carona, Anthony; Jacobson, David; Hildebolt, Charles F.; Qureshi, Waqar; Rowland, Kevin C. (Frontiers in Gastroenterology, 2022)
Background and Aims: Probiotics are widely used and prescribed to address a host of health issues. Despite evidence that different probiotic bacteria have differing therapeutic mechanisms of action, many probiotics are prescribed indiscriminately, with little research to support the use of specific formulations for a given ailment. Further investigation is required to assess the efficacy of one commonly prescribed probiotic formulation Lactobacillus acidophilus and Lactobacillus bulgaricus (helveticus) – for the treatment of diarrhea. This review seeks to assess whether administration of probiotics composed of L.acidophilus and L. bulgaricus (helveticus) are more effective than placebo in reducing symptoms of diarrhea. Methods: A systematic search of randomized placebo-controlled trials evaluating the effectiveness of combination L. acidophilus and L. bulgaricus in the treatment of diarrhea by any cause was conducted and captured all available studies (n = 2411). After application of exclusion criteria, four studies were identified as suitable for inclusion. Separate meta-analyses were conducted for the proportion of cases with diarrhea in the placebo group and the treatment group. To assess differences in proportions between the placebo and treatment groups, a generalized linear model assessment was performed. Results: Analyses revealed the overall proportion of cases with diarrhea in the treatment group, 36 participants who had diarrhea out of 91 total, was only 3.5% lower than the overall proportion in the placebo group, 44 participants who had diarrhea out of 105 total.(P = 0.508), with our considering that the 3.5 lower percentage to be of little or no clinical importance. Conclusion: Existing literature suggests little or no clinical benefit of a L. acidophilus and L. bulgaricus probiotic formulation for the treatment of diarrhea, highlighting the need for more research or re-evaluation of its widespread use.